Security in space : the next generation : conference report 31 March-1 April 2008 (United Nations, 2008)
"This conference looked at ways to build trust in space activities in the future as well as how to move from confrontation to cooperation as a way to increase space security and improve access to outer space for peaceful activities. Participants and presenters discussed the need for new internationals legal instruments, with specific reference to the Chinese-Russian proposal for a Treaty on the Prevention of the Placement of Weapons in Outer Space, the Threat or Use of Force against Outer Space Objects"--Page 4 of cover